MEASURING THE READINESS OF THE UNIVERSITY OF BABYLON TO IMPLEMENT THE KNOWLEDGE MANAGEMENT PROGRAM IN ITS INSTITUTIONAL WORK - Ramah, Ihsan (Revista Inclusiones, 2019)
The study aims to demonstrate the readiness of the University of Babylon to enter the knowledge management program. The questionnaire was used by a scale developed by the American Association for Training and Development (ASTD) to measure the readiness of the organizations to enter the knowledge management program with a sample of (90) of department head and a division in the presidency of the University of Babylon and the colleges affiliated with it under the curriculum of the case study, The study found that the university is close to this and needs to consider some of its institutional issues.